2008
DOI: 10.1002/cne.21798
|View full text |Cite
|
Sign up to set email alerts
|

Retinal anatomy and visual performance in a diurnal cone‐rich laboratory rodent, the Nile grass rat (Arvicanthis niloticus)

Abstract: Unlike laboratory rats and mice, muridae of the Arvicanthis family (A. ansorgei and A. niloticus) are adapted to functioning best in daylight. To date, they have been used as experimental models mainly in studies of circadian rhythms. However, recent work aimed at optimizing photoreceptor-directed gene delivery vectors (Khani et al. [2007] Invest Ophthalmol Vis Sci 48:3954-3961) suggests their potential usefulness for studying retinal pathologies and therapies. In the present study we analyzed the retinal anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 92 publications
5
42
0
Order By: Relevance
“…In contrast to these models, the Nile grass rat possesses one distinctive feature, a higher proportion of cone photoreceptors compared with its nocturnal relatives. Cone photoreceptors are larger than rods and are almost evenly distributed throughout the retina (Bobu et al, 2006;Gaillard et al, 2008Gaillard et al, , 2009. With regard to these characteristics, Nile grass rats may be particularly relevant models for therapies aimed at preserving daylight vision (Cronin et al, 2007;Khani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these models, the Nile grass rat possesses one distinctive feature, a higher proportion of cone photoreceptors compared with its nocturnal relatives. Cone photoreceptors are larger than rods and are almost evenly distributed throughout the retina (Bobu et al, 2006;Gaillard et al, 2008Gaillard et al, , 2009. With regard to these characteristics, Nile grass rats may be particularly relevant models for therapies aimed at preserving daylight vision (Cronin et al, 2007;Khani et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to common mice and rats, these herbivorous and gregarious rodents exhibit a predominantly diurnal pattern of activity during which they maintain multiple runways outside their burrows (Katona and Smale, 1996;McElhinny et al, 1997). Recent investigations performed independently in two Arvicanthis species showed that these animals had significantly more cones in their retina ($30-40% of all photoreceptors; Bobu et al, 2006;Gaillard et al, 2008) than mice and rats ($1-3% of the photoreceptor population; Szel and R€ ohlich, 1992;Mayhew and Astle, 1997;Jeon et al, 1998), had higher visual acuity than the latter (1.3 vs. 0.54 cycles/degree, respectively; Gaillard et al, 2008), and had flicker fusion frequency similar to that of humans (!60 Hz; Gilmour et al, 2008). As in other diurnal rodents (ground squirrel, degu, aguti), there is no foveal specialization in the retina of Nile grass rats (Gaillard et al, 2009).…”
mentioning
confidence: 94%
“…Emerging models of cone-rich mouse and rat strains may provide future opportunities for in vivo study. [121][122][123][124] Ultimately, improving our understanding of cone structure and function will assist in developing therapies that protect cones.…”
Section: Discussionmentioning
confidence: 99%
“…Van Hooser and Nelson, 2006;Gaillard et al, 2008Gaillard et al, , 2009Rocha et al, 2009; for review see Solovei et al, 2009]. Interestingly, relatively closely related species in the Sciuridae family, while sharing a common diurnal lifestyle, can differ dramatically in other dimensions such as terrain niche ( fig.…”
Section: Visual Areasmentioning
confidence: 99%